Concomitant 3D-radiotherapy (3D-RT) with cisplatin (P) for advanced paranasal sinus carcinoma - Crvenkova, Simonida; Krstevska, Valentina; Kraleva, S.; Stojkovski, Igor (American Society of Clinical Oncology (ASCO), 2005)
Background: To determine the benefit of concomitant 3D-RT with P on locoregional control in-patients (pts) with locally advanced paranasal sinus carcinoma. Methods: 6 pts with histopathologically proven carcinoma of the maxillary sinuses and residual macroscopic tumor were treated with combined P (30 mg/m2once per week(w)) and 3D-RT. All pts had undergone surgical reduction. The isocenric 3D technique consisted of several unwedged or wedged beams using 6-MV photon beams. The prescribed total dose at the isocenter was 66–70 Gy in fraction of 2 Gy. The clinical target volume (CTV) was determined according to the CT/MRI findings of the gross tumor volume (GTV). We were considered edges of the resections and regions with residual disease in which the GTV had invaded surround structures. In those regions in which the GTV was limited by intact bone, no margin was added in that direction. In the regions in which the GTV had invaded other paranasal sinuses the whole compartment was included in the CTV. In those regions in which the GTV had invaded the orbit or extended intracranially margin of 0.5–1 sm. was added to the GTV. A 3-mm expansion margin was applied to the CTV to obtain the planning target volume (PTV). All pts were closely followed with clinical examination and control MRI scans in intervals of 6 w and 3 months (m), then 6 m after therapy. Treatment related acute and late side effects ware assessed according to the Common Toxicity Criteria (CTC). Results: Median follow-up was 10 m. One pt developed locoregional recurrence 9 m after therapy. Actuarial locoreginal control rate was 83.33%, with locoregional recurrence of 16.67%. Most common acute side effects were skin erythema CTC Grade 1 in all pts and mucositis Grade 2 and 3. Mild xerostomia was persistent in all pts. Hematological toxicity was low with anemia Grade 1 in 2 pts and leucopenia grade 2 in 3 pts. Conclusions: Our preliminary data indicate that concomitant P and 3 D-RT is feasible and effective in pts with locally advanced paranasal carcinoma. Acute and late toxicity is moderate. Here, P has radiosensitisizing potential and 3D-RT brings opportunity for substantial decrease in the irradiated volume. No significant financial relationships to disclose.